Effects of Sparassis latifolia neutral polysaccharide on immune activity via TLR4-mediated MyD88-dependent and independent signaling pathways in RAW264.7 macrophages - Qiao, Zening; Zhao, Yue; Wang, Menghao; Cao, Jinling; Chang, Mingchang; Yun, Shaojun; Cheng, Yanfen; Cheng, Feier; Feng, Cuiping (Frontiers in Nutrition, 2022)
Background Sparassis latifolia (S. latifolia) is a precious edible fungus with multiple biological activities. To date, no study has been investigated the underlying molecular mechanism of immunoregulation caused by the neutral polysaccharide of S. latifolia. Materials and methods To investigate immunomodulatory mechanism of S. latifolia neutral polysaccharide (SLNP), SLNP was obtained from S. latifolia and its structure, immune receptors and regulation mechanism were studied. Results S. latifolia neutral polysaccharide consisted of arabinose, galactose, glucose, xylose, and mannose with a molar ratio of 6:12:63:10:5. SLNP was a pyran polysaccharide with a relative molecular weight of 3.2 × 105 Da. SLNP promoted the proliferation of RAW264.7, which further induced the secretions of nitric oxide, TNF-α, IL-6, and IFN-β, and upregulated the immune receptor TLR4 expression. Moreover, SLNP increased remarkably the levels of TRAF6, IRF3, JNK, ERK, p38, and p38 mRNA and protein mediated by TLR4. Conclusion S. latifolia neutral polysaccharide regulated the immune function of RAW264.7 through MyD88-dependent and -independent signaling pathways mediated by TLR4 receptor, which suggests that SLNP is a new immunomodulator.